Analysis Of Nutritional Content in Petai (Parkia Speciosa Hassk.) With Various Food Processing Methods - Sisca Ulivia; Sugeng Maryanto; Indri Mulyasari (UNIVERSITAS NGUDI WALUYO, 2021)
Petai (Parkia speciosa Hassk.) is a plant commonly grown and consumed in Indonesia. Indonesian people usually consume Petai in fresh or processed form such as boiled and fried which can be used as an alternative sources of energy and potassium. This research aim to analyze protein, fat, carbohydrate and potassium content in Petai with various food processing methods This study used descriptive analytic design. The objects of this research used Petai were obtained from Kedung District, Jepara Regency, Central Java Province. This treatment used on this research were are fresh Petai, boiled Petai and fried Petai. Processing techniques performed were boiling and frying Petai with the skin until the processing was complete, stripping the skin of Petai seeds, next step is the Petai seeds were tested for nutritional content, analysis of nutrient protein content by kjeldahl method, fat content by soxhlet method, carbohydrate content by difference method and potassium content by Atomic Absorption Spectrometry method. Analysis of nutrient content was conducted at Chemistry Laboratory, Satya Wacana Cristian University, Salatiga.The highest protein content was found in boiled Petai (11.59g / 100g), and the lowest was found in fried Petai (4.96g / 100g). The highest fat content was found in fried Petai (0.75g / 100g), and the lowest was found in fresh Petai (0.15g / 100g). The highest carbohydrate content was found in fried Petai (80g / 100g), and the lowest was found in boiled Petai (63.7g / 100g). The highest potassium content was found in boiled Petai (143mg / 100g), and the lowest was found in fried Petai (106mg / 100g) he highest protein and potassium content was found in boiled Petai, while the highest fat and carbohydrate content was found in fried Petai